ความเชื่อและแบบแผนการดื่มเครื่องดื่มแอลกอฮอล์ของเยาวชนหญิง: Beliefs and Patterns of Alcoholic Drinking Among Female Youth - Homsin, Pornnapa; Srisuriyawet, Rungrat (Asian Health, Science and Technology Reports, 2011)